Remote Teaching Strategies in Writing Skill Development Due to Covid-19 Pandemic - Hernina Dewi Lestari; Sri Fatmaning Hartatik (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Covid-19 pandemic inevitably affects educational practices including in teaching writing. It leads to the unfamiliar challenges for those who are in charge, in this case English instructors. Conducted using descriptive qualitative design, this study aims at describing teaching writing strategies to make high-impact improvement for students' writing performance despite their teaching and learning process has to deal with technological and technical challenges. Thus, the researchers suggested several points to focus on; they were punchy topic selection, meaningful purpose, detailed instruction, excellent feedback, peer review to improve metacognition, and reasonable-targetted grading. The researchers found that teaching strategies that were reasonably effective in virtual classroom were choosing punchy topic to gather the students' interest in developing their writing, delivering meaningful purpose of writing to set the boundaries to make a high quality writing, preparing detailed instruction to minimize any misinterpretation from the students, giving excellent feedback so that the students' writing were thoroughly appreciated and corrected, including peer review section to gain metacognition practice, and setting reasonable-targetted grading to motivate the students without giving burden. Even though the strategies may be particular to remote context, additional research result in face-to-face setting is welcomed to enrich the knowledge development especially in teaching writing.